Time distribution of injury-related in-hospital mortality in a trauma referral center in South of Iran (2010–2015). Issue 21 (May 2017) - Abbasi, Hamidreza; Bolandparvaz, Shahram; Yadollahi, Mahnaz; Anvar, Mehrdad; Farahgol, Zahra
Abstract : Abstract: In Iran, there are no studies addressing trauma death timing and factors affecting time of death after injuries. This study aimed to examine time distribution of trauma deaths in an urban major trauma referral center with respect to victims' injury characteristics during 2010 to 2015. This was a cross-sectional study of adult trauma-related in-hospital deaths resulting from traffic-related accidents, falls, and violence-related injuries. Information on injury characteristics and time interval between admission and death was extracted from 3 hospital databases. Mortality time distribution was analyzed separately in the context of each baseline variable. A total of 1117 in-hospital deaths (mean age 47.6 ± 22.2 years, 80% male) were studied. Deaths timing followed an extremely positive skewed bimodal distribution with 1 peak during the first 24 hours of admission (41.6% of deaths) and another peak starting from the 7th day of hospitalization to the end of first month (27.7% of total). Subjects older than 65 years were more likely to die after 24 hours compared to younger deceased ( P  = .031). More than 70% of firearm-related deaths and 48% of assault-related mortalities occurred early, whereas 67% and 66% of deaths from falls and motorcycle accidents occurred late ( P  < .001). Over 57% of deaths from severe thoracic injuries occurred early, whereas this value was only 37% for central nervous system injuries ( P  < .001). From 2010 to 2015, percentage of late deaths decreased significantly from 68% to 54% ( P  < .001). Considering 1 prehospital peak of mortality and 2 in-hospital peaks, mortality time distribution follows the old trimodal pattern in Shiraz. This distribution is affected by victims' age, injury mechanism, and injured body area. Although such distribution reflects a relatively lower quality of care comparing to mature trauma systems, a change toward expected bimodal pattern has started.